2011
DOI: 10.1517/17425247.2011.574122
|View full text |Cite
|
Sign up to set email alerts
|

Drug delivery systems in the treatment of African trypanosomiasis infections

Abstract: The design of drug formulations relevant to the treatment of AT must include a combination of very specific properties. In summary, the drug delivery system must be compatible with the physicochemical properties of the drug (charge, lipophilicity and molecular mass) in order to allow high drug payloads while being biocompatible for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…Recent studies have also shown that colloidal nanoparticle formulations of diminazene exhibited greater activity against T. brucei brucei in vitro and had increased delivery to the brain in mice (Kroubi et al. , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that colloidal nanoparticle formulations of diminazene exhibited greater activity against T. brucei brucei in vitro and had increased delivery to the brain in mice (Kroubi et al. , ).…”
Section: Resultsmentioning
confidence: 99%
“…It would, therefore, be of interest to conduct similar studies to establish the protective or curative effects of diminazene aceturate compared to the appropriate control groups. Recent studies have also shown that colloidal nanoparticle formulations of diminazene exhibited greater activity against T. brucei brucei in vitro and had increased delivery to the brain in mice (Kroubi et al 2010(Kroubi et al , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…So far, chemotherapy is the only strategy available to treat the disease, whereby unique organelles of trypanosomes (glycosomes or kinetoplast) that are absent in the mammalian host or trypanosome metabolic pathways that differ from their host counterparts (carbohydrate metabolism, protein and lipid modifications, and programmed cell death) are targeted (2527). Given that chemotherapy is associated with high drug toxicity, there is an urgent need to optimize trypanocide usage and delivery in order to decrease the risk of toxicity and/or resistance development (2830). Control of AT is also hampered due to inefficient diagnosis of the infection especially for AAT and T. b. rhodesiense HAT where microscopical parasite detection (cheap but with low sensitivity), detection of the parasite’s DNA (expensive but with high sensitivity), or anti-parasite antibodies remain the only available tools for diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Single-drug use is customarily used for AAT management, but there's renewed interest in development of novel biocompatible formulations that improve therapeutic outcomes (Kroubi et al ., 2011; Giordani et al ., 2016). Randomized clinical trials are necessary to evaluate the benefits and adverse effects attributable to these novel treatments.…”
Section: Discussionmentioning
confidence: 99%